Disease Activity Patterns of Crohn's Disease in the First Ten Years After Diagnosis in the Population-based IBD South Limburg Cohort. (26th August 2020) - Wintjens, Dion; Bergey, Francois; Saccenti, Edoardo; Jeuring, Steven; van den Heuvel, Tim; Romberg-Camps, Mariëlle; Oostenbrug, Liekele; Masclee, Ad; Martins dos Santos, Vitor; Jonkers, Daisy; Pierik, Marie
Abstract: Background and Aims: Real-life data on long-term disease activity in Crohn's disease [CD] are scarce. Most studies describe disease course by using proxies, such as drug exposure, need for surgery or hospitalisations, and disease progression. We aimed to describe disease course by long-term disease activity and to identify distinctive disease activity patterns in the population-based IBD South Limburg cohort [IBDSL]. Methods: All CD patients in IBDSL with ≥10 years follow-up [ n = 432] were included. Disease activity was defined for each yearly quarter by mucosal inflammation on endoscopy or imaging, hospitalisation, surgery, or treatment adjustment for increased symptoms. Six distinct disease activity clusters were defined. Subsequently, the associations between clinical characteristics and the patterns were assessed using multivariable logistic regression models. Results: On average, patients experienced 5.44 (standard deviation [SD] 3.96) quarters of disease activity during the first 10 years after diagnosis. Notably, 28.2% of the patients were classified to a quiescent pattern [≤2 active quarters in 10 years], and 89.8% of those never received immunomodulators nor biologics. Surgery at diagnosis (odds ratio [OR] 2.99; 95% confidence interval [CI] 1.07–8.34) and higher age [OR 1.03; 95% CI 1.01–1.06] were positively associated with the quiescent pattern, whereas inverse associations were observed for ileocolonic location [OR 0.44; 95% CI 0.19–1.00], smoking [OR 0.43; 95% CI 0.24–0.76] and need for steroids <6 months [OR 0.24; 95% CI 0.11–0.52]. Conclusions: Considering long-term disease activity, 28.2% of CD patients were classified to a quiescent cluster. Given the complex risk-benefit balance of immunosuppressive drugs, our findings underline the importance of identifying better predictive markers to prevent both over-treatment and under-treatment.